2020
DOI: 10.1590/s2179-975x9519
|View full text |Cite|
|
Sign up to set email alerts
|

Zooplankton trajectory before, during and after a hydropower dam construction

Abstract: Aim Understanding the impact of anthropogenic activities is central for supporting management and conservation efforts. In aquatic ecosystems, the construction of dams for hydroelectric power plants is a major environmental change that turns the riverine ecosystem into a reservoir lake. Such environmental deep alteration causes profound impacts in biota. The goal of this study is to make a comprehensive description of zooplankton trajectory following the construction of a reservoir in the transition from the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Schmidt et al [18] described zooplankton as a key biological group that is very important to the functioning of the ecosystem. They respond strongly to environmental changes and are used to assess the conditions in aquatic ecosystems [18,19]. Temporal and spatial variations of physico-chemical environmental conditions often result in dramatic and rapid changes in zooplankton because of their short life span and fast regeneration [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmidt et al [18] described zooplankton as a key biological group that is very important to the functioning of the ecosystem. They respond strongly to environmental changes and are used to assess the conditions in aquatic ecosystems [18,19]. Temporal and spatial variations of physico-chemical environmental conditions often result in dramatic and rapid changes in zooplankton because of their short life span and fast regeneration [20].…”
Section: Introductionmentioning
confidence: 99%
“…Zooplankton are microscopic animals that are essential components of aquatic food webs; an important link in the conversion of energy from producers to consumers [16,17]. Schmidt et al [18] described zooplankton as a key biological group that is very important to the functioning of the ecosystem. They respond strongly to environmental changes and are used to assess the conditions in aquatic ecosystems [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…One of the essential biological communities found in lotic freshwater ecosystems is zooplankton. Zooplankton is microscopic animals that serve as an important link in the conversion of energy from producers to consumers; playing an essential role in the aquatic food webs (Sharma et al, 2010;Schmidt et al, 2020). Zooplanktons are weak swimmers and usually drift along with the currents (Prygiel and Coste, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the damming of the river had a negative effect on the phytoplankton communities, reducing their richness and density during the postdam period of the Tocantins River. Previous studies in the same field have also shown that damming impacts phytoplankton and zooplankton communities (Lu et al 2020;Silva et al 2020;Schmidt et al 2020;Silva et al 2023).…”
Section: Discussionmentioning
confidence: 69%